2017
DOI: 10.1016/j.bjm.2016.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of polycyclic aromatic hydrocarbon (PAH) compounds: (acenaphthene and fluorene) in water using indigenous bacterial species isolated from the Diep and Plankenburg rivers, Western Cape, South Africa

Abstract: This study was conducted to investigate the occurrence of PAH degrading microorganisms in two river systems in the Western Cape, South Africa and their ability to degrade two PAH compounds: acenaphthene and fluorene. A total of 19 bacterial isolates were obtained from the Diep and Plankenburg rivers among which four were identified as acenaphthene and fluorene degrading isolates. In simulated batch scale experiments, the optimum temperature for efficient degradation of both compounds was determined in a shakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Various hydrocarbon-degrading bacteria have been isolated to date from Antarctica, including Rhodococcus, Acinetobacter, Pseudomonas , and Sphingomonas species (Aislabie et al, 2006 ). The use of serial PAH-supplemented growth media enrichments, and the highly selective growth condition of utilizing PAHs as sole energy source, have permitted to establish successful approaches to isolate nalovel PAH-degrading bacteria of interest from varied environmental sources (Obi et al, 2016 ; Alegbeleye et al, 2017 ; Li et al, 2017 ; Oyehan and Al-Thukair, 2017 ). Additionally, new techniques of in situ microculturing have allowed to culture an even broader number of PAH-degrading organisms by recreating the native conditions of growth, allowing growth of bacteria not normally isolated using standard culture conditions (van Dorst et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various hydrocarbon-degrading bacteria have been isolated to date from Antarctica, including Rhodococcus, Acinetobacter, Pseudomonas , and Sphingomonas species (Aislabie et al, 2006 ). The use of serial PAH-supplemented growth media enrichments, and the highly selective growth condition of utilizing PAHs as sole energy source, have permitted to establish successful approaches to isolate nalovel PAH-degrading bacteria of interest from varied environmental sources (Obi et al, 2016 ; Alegbeleye et al, 2017 ; Li et al, 2017 ; Oyehan and Al-Thukair, 2017 ). Additionally, new techniques of in situ microculturing have allowed to culture an even broader number of PAH-degrading organisms by recreating the native conditions of growth, allowing growth of bacteria not normally isolated using standard culture conditions (van Dorst et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed that degradation of PAHs by Aeromonas hydrophila , Bacillus megaterium , Raoultella ornithinolytica , and Serratia marcescens recorded over 90% degradation efficiency for fluorene and acenaphthene (Alegbeleye, Opeolu, & Jackson, 2017). However, certain environmental variables such as temperature and pH were reported to have a considerable influence on the efficiency of the bioremediation processes.…”
Section: Bioremediationmentioning
confidence: 99%
“…The use of microorganisms for remediation of PAHs has been regarded as the main natural degradation method in soils, as native microorganisms could utilize bioavailable PAHs as their sole source of carbon ( Haritash and Kaushik, 2009 ). Several bacterial species ( Acinetobacter , Alcanivorax , Cellulomonas , Deitzia , Micrococcus , Marinobacter , Pseudomonas , Paenibacillus , Sphingomonas ) have been reported for degrading PAHs ( Maki et al, 2010 ; Alegbeleye et al, 2017 ). Mycobacterium spp.…”
Section: Introductionmentioning
confidence: 99%